Composite gel electrolyte membrane, preparation method thereof and secondary battery
By modifying the oxide solid electrolyte particles and preparing composite gel electrolyte membranes, the challenges of oxide solid electrolyte in terms of interface stability, production cost and electrochemical window compatibility are solved, and the performance and energy density of the battery are improved.
Patent Information
- Application Number
- CN202411977322.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
AI Technical Summary
Oxide solid electrolytes have challenges in interface stability, production costs, and electrochemical window compatibility, affecting battery performance and energy density.
By modifying the oxide solid electrolyte particles, a single-oriented gel frame is prepared and sintered, ground into modified solid electrolyte particles, and a porous composite solid electrolyte membrane is prepared by combining polymer as a matrix material, and swelling is achieved by dropping electrolyte solution to obtain a composite gel electrolyte membrane.
It improves the fast charging and discharging performance, voltage stability and cycling performance of the battery, reduces the preparation cost, and enhances the mechanical strength and dimensional stability of the electrolyte membrane.
Smart Images

Figure CN119674214A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a composite gel electrolyte membrane and a preparation method thereof, and a secondary battery. Background Art
[0002] Oxide solid electrolytes have extremely high energy density because they can use ideal lithium metal negative electrodes, but oxide solid electrolytes have disadvantages. Interface stability problems: the interface stability between oxide solid electrolytes and electrode materials is poor, which may lead to poor contact and increased interface impedance, affecting battery performance; high production cost: the production process of oxide solid electrolytes is complicated, and some raw materials are expensive, resulting in high production costs and fragility; electrochemical window limitation: the electrochemical window of oxide solid electrolytes may limit compatibility with high-voltage positive electrode materials, affecting the overall energy density of the battery. Summary of the invention
[0003] In order to solve the above technical problems, the present application provides a composite gel electrolyte membrane and a preparation method thereof, and a secondary battery.
[0004] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, the present invention provides a method for preparing a composite gel electrolyte membrane, comprising: S1. dispersing oxide solid electrolyte particles in a solvent to obtain a suspension; transferring the suspension to an environment containing liquid nitrogen and freezing it, so that ice crystals grow vertically from bottom to top in the suspension to obtain a single-oriented gel skeleton; S2, freeze-drying the single-oriented gel skeleton to obtain an aerogel; sintering the obtained aerogel under a protective atmosphere to obtain a porous solid electrolyte, and grinding the porous solid electrolyte to obtain modified solid electrolyte particles; S3, mixing and stirring the modified solid electrolyte particles, PEO and solvent to obtain slurry, preparing the slurry into a film, and drying the film to obtain a porous composite solid electrolyte membrane; and dripping an electrolyte into the porous composite solid electrolyte membrane to obtain a composite gel electrolyte membrane.
[0005] In a second aspect, a composite gel electrolyte membrane is provided, which is prepared by the aforementioned preparation method.
[0006] The third invention provides a secondary battery comprising the composite gel electrolyte membrane.
[0007] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The present invention performs modification treatment on solid electrolyte particles, prepares the solid electrolyte particles into a suspension, prepares a single-oriented aerogel and then sinters, grinds the sintered product into particles, obtains modified solid electrolyte particles with uniform particle size dispersion and uniform composition, uses a polymer as a matrix material and the modified solid electrolyte particles as a dispersion material to prepare a porous composite solid electrolyte membrane, and then drips an electrolyte to achieve swelling to obtain a composite gel electrolyte membrane. A battery assembled with the prepared composite gel electrolyte membrane exhibits better rapid charge and discharge performance, and voltage stability and cycle performance are also improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0009] Figure 1 This is the element distribution diagram of the oxide particles prepared in step S3 of Example 1.
[0010] Figure 2 This is a SEM image of the cross-section of the porous composite solid electrolyte membrane prepared in Example 1.
[0011] Figure 3 This is a SEM image of the surface of the porous composite solid electrolyte membrane prepared in Example 1.
[0012] Figure 4 This is the SEM image of the porous polymer electrolyte membrane prepared in Comparative Example 1.
[0013] Figure 5 The electrochemical cycle performance diagram of the battery assembled with the gel electrolyte membrane prepared in Example 1 and Comparative Examples 1-2.
[0014] Figure 6 This is a rate performance diagram of batteries assembled with gel electrolyte membranes prepared in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0015] Some embodiments of the present invention provide a method for preparing a composite gel electrolyte membrane, comprising: S1. dispersing oxide solid electrolyte particles in a solvent to obtain a suspension; transferring the suspension to an environment containing liquid nitrogen and freezing it, so that ice crystals grow vertically from bottom to top in the suspension to obtain a single-oriented gel skeleton; S2, freeze-drying the single-oriented gel skeleton to obtain an aerogel; sintering the obtained aerogel under a protective atmosphere to obtain a porous solid electrolyte, and grinding the porous solid electrolyte to obtain modified solid electrolyte particles; S3, mixing and stirring the modified solid electrolyte particles, PEO and solvent to obtain slurry, preparing the slurry into a film, and drying the film to obtain a porous composite solid electrolyte membrane; and dripping an electrolyte into the porous composite solid electrolyte membrane to obtain a composite gel electrolyte membrane.
[0016] The porous composite solid electrolyte membrane prepared by composite polymer and oxide solid electrolyte particles has more crystal defects, which improves the migration number of lithium ions; at the same time, the addition of electrolyte makes the electrolyte gel (the composite electrolyte membrane finally obtained becomes gel through swelling), increases the transmission channel of lithium ions, reduces the interface resistance between the electrode and the electrolyte, and also increases the toughness of the gel electrolyte; and the oxide solid electrolyte can increase the number of pores in the gel electrolyte, provide more abundant liquid channels, and thus has better fast charging performance. The rich pore structure inside the porous composite solid electrolyte membrane can firmly lock the liquid electrolyte part, thereby maintaining a high ionic conductivity, and the oxide solid electrolyte particles enhance the mechanical strength and dimensional stability of the gel electrolyte membrane, which can resist the growth of lithium dendrites to a certain extent, reduce the short circuit risk caused by lithium dendrites piercing the diaphragm, improve the fast charging and discharging performance, and also have a good improvement on voltage stability and cycle performance. The preparation process is simple, the synthesis temperature is low, and the preparation cost is reduced.
[0017] And by modifying the oxide solid electrolyte particles, specifically, the solid electrolyte particles are formulated into a suspension and prepared into a single-oriented aerogel, and then low-temperature sintering is performed, and the low-temperature sintering product is ground into particles to obtain modified solid electrolyte particles; a polymer is used as a matrix material, and the modified solid electrolyte particles are used as a dispersion material to prepare a porous composite solid electrolyte membrane, and swelling is achieved by dripping an electrolyte to prepare a composite gel electrolyte membrane, and the obtained composite gel electrolyte has good uniformity of components and is uniform and dense as a whole; the cycle performance and rate performance of a battery assembled with the composite gel electrolyte membrane prepared using the modified oxide solid electrolyte particles as raw materials are further improved.
[0018] It is worth noting that in the above preparation method, the electrolyte can be any conventional organic electrolyte in the art, such as Li037 (1.0M LiPF6in EC:DEC:EMC=1:1:1 Vol%), and of course other conventional organic electrolytes can also be used.
[0019] In some preferred embodiments, in step S1, the particle size of the solid electrolyte particles is 1-1.2 μm, such as 1 μm, 1.1 μm, 1.2 μm, etc.
[0020] In some preferred embodiments, in step S1, the dispersion is mechanical stirring dispersion or ultrasonic dispersion.
[0021] In some preferred embodiments, in step S1, the solvent is a mixed solution prepared by mixing water and an organic solvent in a volume ratio of 1:8-9, for example, 1:8, 1:8.2, 1:8.5, 1:8.8, 1:9, etc.; and the organic solvent is anhydrous ethanol or N-methylpyrrolidone.
[0022] In some preferred embodiments, in step S1, the solid-liquid mass ratio of the suspension is 1:40-50, for example, 1:40, 1:42, 1:45, 1:48, 1:50, etc.
[0023] In some preferred embodiments, in step S1, the suspension is transferred to an environment containing liquid nitrogen for freezing, so that ice crystals grow vertically from bottom to top in the suspension to obtain a single-oriented gel skeleton, which includes: transferring a container containing the suspension to a mold containing liquid nitrogen, wherein a heat-conducting sheet or a heat-conducting platform extending out of the liquid nitrogen surface is provided in the liquid nitrogen, and the container is placed on the heat-conducting sheet or the heat-conducting platform, and after freezing, a single-oriented gel skeleton is obtained. The material of the heat-conducting sheet or the heat-conducting platform can be a heat-conducting material such as metal.
[0024] In some preferred embodiments, in step S2, the sintering temperature is 200-500°C, for example, 200°C, 220°C, 250°C, 280°C, 300°C, 320°C, 350°C, 380°C, 400°C, 420°C, 450°C, 480°C, 500°C, etc.
[0025] In some preferred embodiments, in step S2, the sintering heat preservation time is 3 to 5 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc.
[0026] In some preferred embodiments, in step S2, the heating rate of sintering is 2-4°C / min, for example, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, etc.
[0027] In some preferred embodiments, in step S2, the protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere.
[0028] In some preferred embodiments, in step S3, the particle size of the modified solid electrolyte particles is 1-1.2 μm, such as 1 μm, 1.1 μm, 1.2 μm, etc.
[0029] In some preferred embodiments, in step S3, the mass ratio of the modified solid electrolyte particles to PEO is 1 to 3:4, for example, 1:3, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4, etc.
[0030] In some preferred embodiments, in step S3, in the slurry, the mass of the solvent is 12 to 20 times the mass of PEO, for example, 12 times, 13 times, 14 times, 15 times, 16 times, 17 times, 18 times, 19 times, 20 times, etc.
[0031] In some preferred embodiments, in step S3, the solvent is one of acetonitrile, tetrahydrofuran, ethylene glycol, and N-methylpyrrolidone.
[0032] In some preferred embodiments, in step S1, the oxide solid electrolyte is Li 7-z Ln3Z 2-z Ta z O 12 , where the value of z is 0≤z≤1, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, etc.
[0033] In some preferred embodiments, in step S1, the method for preparing the oxide solid electrolyte particles comprises: mixing, ball-milling, sintering and grinding the metal sources corresponding to the metal elements contained in the solid electrolyte.
[0034] It is worth noting that the metal source corresponding to the metal element contained in the solid electrolyte, for example, when the solid electrolyte is Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 When the metal source Li source, La source, Zr source, Ta source of the metal elements contained therein are used as raw materials, wherein the metal source (Li source, La source, Zr source, Ta source) can be a conventional metal source for preparing solid electrolytes in the art, which will not be described in detail here; the mixed ball milling can be dry ball milling or wet ball milling, preferably wet ball milling, which needs to be conventionally dried after wet ball milling, and then conventionally ground to improve the dispersion of the material. The sintering temperature can be the conventional sintering temperature for preparing solid electrolyte materials in the art, such as sintering to prepare Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 When heating, first raise the temperature to 1350℃ and keep it for 30min, then lower the temperature to 150℃ and keep it for 300min.
[0035] In some preferred embodiments, step S3 further includes the step of cutting the porous composite solid electrolyte membrane.
[0036] In some preferred embodiments, in step S3, the film is prepared by using an existing film preparation method, such as any one of a casting method, a coating method, a solution method, and the like.
[0037] Some embodiments of the present invention provide a composite gel electrolyte membrane, which is prepared by the aforementioned preparation method.
[0038] Some embodiments of the present invention provide a secondary battery including the composite gel electrolyte membrane.
[0039] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0040] Example 1 A method for preparing a composite gel electrolyte membrane, comprising: S1. 2.64 g of lithium carbonate, 4.89 g of lanthanum oxide, 1.86 g of zirconium oxide, 1.1 g of tantalum oxide, and 30 g of isopropanol were ball-milled in a ball mill at a speed of 400 rpm for 1200 min. The ball-milled materials were placed in an oven and dried at 70 ° C. After drying, they were ground into fine particles and sintered in a muffle furnace in a nitrogen / argon atmosphere. The temperature was raised to 1350 ° C within 270 min, and the temperature was kept at this temperature for 30 min. Then, the temperature was lowered to 150 ° C within 240 min, and the temperature was kept at this temperature for 300 min before sintering to obtain a solid electrolyte Li 6.5 LqCy 1.5 Ta 0.5 O 12 .
[0041] S2, grinding the sintered material into fine particles with a particle size of about 1000-1200 nm, and then ultrasonically dispersing them in a solvent with a solid-liquid mass ratio of 1:50, and stirring to obtain a suspension; the solvent is deionized water and anhydrous ethanol prepared in a volume ratio of 1:8; S3. Transfer the container containing the suspension to a mold filled with liquid nitrogen. The liquid nitrogen is provided with a copper heat conductive sheet extending out of the liquid nitrogen surface. The container is placed on the copper heat conductive sheet and frozen to allow ice crystals in the suspension to grow vertically from bottom to top to obtain a single-oriented gel skeleton; freeze-dry the single-oriented gel skeleton to obtain an aerogel; sinter the aerogel in an inert atmosphere and / or a nitrogen atmosphere, heat it to 400°C at a heating rate of 4°C / min and keep it warm for 4 hours to obtain a porous solid electrolyte. After grinding, oxide particles with a particle size of 1000~1200nm are obtained. The element distribution diagram of the obtained oxide particles is as follows: Figure 1 As shown by Figure 1 It can be seen that the elements in the prepared oxide are evenly distributed.
[0042] S4, 0.2g oxide particles were mixed with 0.4g PEO and 6.4g acetonitrile and stirred for 12 hours, and a conventional coating method was used to prepare a thin film, and the film was dried to obtain a thin film. Specifically, a 200μm coater was used to coat on a smooth glass plate, 2g was coated each time, and the film was dried after standing for three times. After standing for three hours, the film was dried in a 60°C vacuum oven. The obtained film was cut into 19mm discs to obtain a composite solid electrolyte membrane; the cross-sectional and front SEM images of the obtained composite solid electrolyte are shown as follows: Figure 2 and Figure 3 As shown, the composite solid electrolyte membrane is a porous electrolyte with a thickness of about 50 μm. The main body is composed of polymer particles and oxide particles, and there is a complex spatial structure inside the electrolyte membrane, which confirms the porous characteristics of the electrolyte membrane.
[0043] S5. Add electrolyte (LB037: 1.0M LiPF6in EC:DEC:EMC=1:1:1 Vol%) dropwise into the porous composite solid electrolyte membrane to form a composite gel electrolyte membrane.
[0044] Comparative Example 1 S1. 0.4 g PEO and 6.4 g acetonitrile were mixed and stirred for 12 hours to prepare a thin film, and then dried to obtain a porous polymer electrolyte membrane. The SEM image is as follows: Figure 4 As shown, the prepared film was cut into 19 mm round pieces; S2. When the original sheet is in contact with the electrolyte (LB037: 1.0M LiPF6in EC:DEC:EMC=1:1:1 Vol%), a gel electrolyte membrane will be formed.
[0045] By comparing the SEM images of the porous electrolyte membranes obtained in Example 1 and Comparative Example 1, it can be seen that the microscopic morphology of the porous composite solid electrolyte membrane in Example 1 presents more pores.
[0046] Comparative Example 2 A method for preparing a composite gel electrolyte membrane, comprising: S1. 2.64 g of lithium carbonate, 4.89 g of lanthanum oxide, 1.86 g of zirconium oxide, 1.1 g of tantalum oxide, and 30 g of isopropanol were ball-milled in a ball mill at a speed of 400 rpm for 1200 min. The ball-milled materials were placed in an oven and dried at 70 ° C. After drying, they were ground into fine particles and sintered in a muffle furnace in a nitrogen / argon atmosphere. The temperature was raised to 1350 ° C within 270 min, and the temperature was kept at this temperature for 30 min. Then, the temperature was lowered to 150 ° C within 240 min, and the temperature was kept at this temperature for 300 min before sintering to obtain a solid electrolyte Li 6.5 LqCy 1.5 Ta 0.5 O 12 .
[0047] S2. Grind the sintered material into fine particles with a particle size of 1000-1200nm, mix 0.2g of oxide particles with 0.4g of PEO and 6.4g of acetonitrile and stir for 12 hours, prepare it into a thin film by conventional coating method, and dry it to obtain a thin film. Specifically, use a 200μm coater to coat on a smooth glass plate, coat 2g each time, let it stand and dry, then coat again, for a total of three times, let it stand and dry, then put it in a 60℃ vacuum oven and dry for 3 hours. The obtained film is cut into 19mm discs to obtain a porous composite solid electrolyte membrane; the prepared film is cut into 19mm discs to obtain a porous composite solid electrolyte membrane; S3. Add electrolyte (LB037: 1.0M LiPF6in EC:DEC:EMC=1:1:1 Vol%) into the porous composite solid electrolyte membrane, and a composite gel electrolyte membrane will be formed after contact.
[0048] Semi-solid battery assembly: The composite gel electrolyte membrane prepared in Example 1 and Comparative Example 2 and the gel electrolyte membrane prepared in Comparative Example 2 were used as electrolytes, respectively. Button cells were assembled in the order of positive electrode shell, positive electrode material (622), porous electrolyte, electrolyte (LB-037), lithium sheet, gasket, shrapnel, and negative electrode shell. After the battery was left to stand for 15 hours, a semi-solid battery was obtained.
[0049] The semi-solid-state battery assembled with the gel electrolyte membrane prepared in Example 1 and Comparative Example 1 and Comparative Example 2 was subjected to a charge and discharge cycle test at 25°C, 2.7V~4.3V, and a test rate of 0.5C. The test results are shown in FIG. Figure 5 shown.
[0050] The semi-solid batteries assembled with the gel electrolyte membranes prepared in Example 1, Comparative Example 1 and Comparative Example 2 have cycle performances of 2.7V~4.3V at different rates at 25°C. Figure 6 shown.
[0051] Depend on Figure 5 and Figure 6 It can be seen that under the same test conditions, the semi-solid batteries assembled with the composite gel electrolyte membranes prepared in Example 1 and Comparative Example 2 have lower low-rate discharge specific capacity than the semi-solid batteries assembled with the gel electrolyte membranes prepared in Comparative Example 1, but the rate performance and cycle stability of the batteries are significantly improved. This indicates that the modification with inorganic solid electrolyte particles is significantly effective in improving the structural stability and high-rate performance of the electrolyte. After analysis, this is because the porous composite solid electrolyte membrane prepared with composite polymer and oxide solid electrolyte particles has more crystal defects than the polymer electrolyte membrane, which improves the migration number of lithium ions. At the same time, the introduced electrolyte The solution makes the electrolyte gel-like, increases the transmission channel of lithium ions, reduces the interfacial resistance between the electrode and the electrolyte, and also increases the toughness of the gel electrolyte; and the oxide solid electrolyte can increase the number of pores in the gel electrolyte, providing more abundant liquid channels, so it has better fast charging performance, and the rich internal pore structure can firmly lock the liquid electrolyte part, thereby maintaining a high ionic conductivity. The oxide solid electrolyte particles have enhanced mechanical strength and dimensional stability, and can resist the growth of lithium dendrites to a certain extent, reducing the risk of short circuit caused by lithium dendrites piercing the diaphragm, thereby improving the battery's rapid charge and discharge performance, voltage stability and cycle performance.
[0052] Depend on Figure 5 and Figure 6 It can also be seen that, under the same test conditions, the semi-solid-state battery assembled with the composite gel electrolyte membrane in Example 1 has better capacity retention and high-rate performance than the semi-solid-state battery assembled with the composite gel electrolyte membrane prepared in Comparative Example 2, indicating that the addition of the modified solid electrolyte particles has a more obvious positive effect on the cycle performance of the battery.
[0053] Example 2 A method for preparing a composite gel electrolyte membrane, comprising: S1. 2.64 g of lithium carbonate, 4.89 g of lanthanum oxide, 1.86 g of zirconium oxide, 1.1 g of tantalum oxide, and 30 g of isopropanol were ball-milled in a ball mill at a speed of 400 rpm for 1200 min. The ball-milled materials were placed in an oven and dried at 70 ° C. After drying, they were ground into fine particles and sintered in a muffle furnace in a nitrogen / argon atmosphere. The temperature was raised to 1350 ° C within 270 min, and the temperature was kept at this temperature for 30 min. Then, the temperature was lowered to 150 ° C within 240 min, and the temperature was kept at this temperature for 300 min before sintering to obtain a solid electrolyte Li 6.5 Ln3Z 1.5 Ta 0.5 O12 .
[0054] S2, grinding the sintered material into fine particles with a particle size of about 1000-1200 nm, and then ultrasonically dispersing them in a solvent with a solid-liquid mass ratio of 1:50, and stirring to obtain a suspension; the solvent is deionized water and anhydrous ethanol prepared in a volume ratio of 1:9; S3. Transferring the container containing the suspension to a mold filled with liquid nitrogen, wherein a copper thermal conductive sheet extending out of the liquid nitrogen surface is provided in the liquid nitrogen, and the container is placed on the copper thermal conductive sheet for freezing, so that ice crystals in the suspension grow vertically from bottom to top to obtain a single-oriented gel skeleton; freeze-drying the single-oriented gel skeleton to obtain an aerogel; sintering the aerogel in an inert atmosphere and / or a nitrogen atmosphere, heating the temperature to 500°C at a heating rate of 4°C / min and keeping the temperature for 4 hours to obtain a porous solid electrolyte, and grinding to obtain oxide particles with a particle size of 1000~1200nm.
[0055] S4, 0.2g oxide particles were mixed with 0.4g PEO and 6.4g acetonitrile for 12 hours, and a conventional coating method was used to prepare a thin film, and the film was dried to obtain a thin film. Specifically, a 200μm coater was used to coat on a smooth glass plate, 2g was coated each time, and the film was dried and then coated again for a total of three times. After drying, the film was placed in a 60°C vacuum oven for 3 hours. The obtained film was cut into 19mm discs to obtain a porous composite solid electrolyte membrane.
[0056] S5. Add electrolyte (LB037: 1.0M LiPF6in EC:DEC:EMC=1:1:1 Vol%) dropwise into the porous composite solid electrolyte membrane to form a composite gel electrolyte membrane.
[0057] Example 3 A method for preparing a composite gel electrolyte membrane, comprising: S1. 2.64 g of lithium carbonate, 4.89 g of lanthanum oxide, 1.86 g of zirconium oxide, 1.1 g of tantalum oxide, and 30 g of isopropanol were ball-milled in a ball mill at a speed of 400 rpm for 1200 min. The ball-milled materials were placed in an oven and dried at 70 ° C. After drying, they were ground into fine particles and sintered in a muffle furnace in a nitrogen / argon atmosphere. The temperature was raised to 1350 ° C within 270 min, and the temperature was kept at this temperature for 30 min. Then, the temperature was lowered to 150 ° C within 240 min, and the temperature was kept at this temperature for 300 min before sintering to obtain a solid electrolyte Li 6.5 LqCy 1.5 Ta 0.5 O 12 .
[0058] S2, grinding the sintered material into fine particles with a particle size of about 1000-1200 nm, and then ultrasonically dispersing them in a solvent with a solid-liquid mass ratio of 1:50, and stirring to obtain a suspension; the solvent is deionized water and anhydrous ethanol prepared in a volume ratio of 1:8; S3. Transferring the container containing the suspension to a mold filled with liquid nitrogen, wherein a copper heat conductive plate extending out of the liquid nitrogen surface is provided in the liquid nitrogen, and the container is placed on the copper heat conductive plate for freezing, so that ice crystals in the suspension grow vertically from bottom to top to obtain a single-oriented gel skeleton; freeze-drying the single-oriented gel skeleton to obtain an aerogel; sintering the aerogel in an inert atmosphere and / or a nitrogen atmosphere, heating the temperature to 400°C at a heating rate of 2°C / min and keeping the temperature for 4 hours to obtain a porous solid electrolyte, and grinding to obtain oxide particles with a particle size of 1000~1200nm.
[0059] S4, 0.1g oxide particles were mixed with 0.4g PEO and 6.4g acetonitrile for 12 hours, and a conventional coating method was used to prepare a thin film, and the film was dried to obtain a thin film. Specifically, a 200μm coater was used to coat on a smooth glass plate, 2g was coated each time, and the film was dried and then coated again for a total of three times. After drying, the film was dried in a vacuum oven at 60°C for 3 hours. The obtained film was cut into 19mm discs to obtain a porous composite solid electrolyte membrane.
[0060] S5. Add electrolyte (LB037: 1.0M LiPF6in EC:DEC:EMC=1:1:1 Vol%) dropwise into the porous composite solid electrolyte membrane to form a composite gel electrolyte membrane.
[0061] Example 4 A method for preparing a composite gel electrolyte membrane, comprising: S1. 2.64 g of lithium carbonate, 4.89 g of lanthanum oxide, 1.86 g of zirconium oxide, 1.1 g of tantalum oxide, and 30 g of isopropanol were ball-milled in a ball mill at a speed of 400 rpm for 1200 min. The ball-milled materials were placed in an oven and dried at 70 ° C. After drying, they were ground into fine particles and sintered in a muffle furnace in a nitrogen / argon atmosphere. The temperature was raised to 1350 ° C within 270 min, and the temperature was kept at this temperature for 30 min. Then, the temperature was lowered to 150 ° C within 240 min, and the temperature was kept at this temperature for 300 min before sintering to obtain a solid electrolyte Li 6.5 LqCy 1.5 Ta 0.5 O 12 .
[0062] S2, grinding the sintered material into fine particles with a particle size of about 1000-1200 nm, and then ultrasonically dispersing them in a solvent with a solid-liquid mass ratio of 1:50, and stirring to obtain a suspension; the solvent is deionized water and anhydrous ethanol prepared in a volume ratio of 1:8; S3. Transferring the container containing the suspension to a mold filled with liquid nitrogen, wherein a copper heat conductive plate extending out of the liquid nitrogen surface is provided in the liquid nitrogen, and the container is placed on the copper heat conductive plate for freezing, so that ice crystals in the suspension grow vertically from bottom to top to obtain a single-oriented gel skeleton; freeze-drying the single-oriented gel skeleton to obtain an aerogel; sintering the aerogel in an inert atmosphere and / or a nitrogen atmosphere, heating the temperature to 400°C at a heating rate of 2°C / min and keeping the temperature for 4 hours to obtain a porous solid electrolyte, and grinding to obtain oxide particles with a particle size of 1000~1200nm.
[0063] S4, 0.3g oxide particles were mixed with 0.4g PEO and 6.4g acetonitrile for 12 hours, and a conventional coating method was used to prepare a thin film, and the film was dried to obtain a thin film. Specifically, a 200μm coater was used to coat on a smooth glass plate, 2g was coated each time, and the film was dried and then coated again for a total of three times. After drying, the film was placed in a vacuum oven at 60°C for 3 hours. The obtained film was cut into 19mm discs to obtain a porous composite solid electrolyte membrane.
[0064] S5. Add electrolyte (LB037: 1.0M LiPF6in EC:DEC:EMC=1:1:1 Vol%) dropwise into the porous composite solid electrolyte membrane to form a composite gel electrolyte membrane.
[0065] Example 5 A method for preparing a composite gel electrolyte membrane, comprising: S1. 2.64 g of lithium carbonate, 4.89 g of lanthanum oxide, 1.86 g of zirconium oxide, 1.1 g of tantalum oxide, and 30 g of isopropanol were ball-milled in a ball mill at a speed of 400 rpm for 1200 min. The ball-milled materials were placed in an oven and dried at 70 ° C. After drying, they were ground into fine particles and sintered in a muffle furnace in a nitrogen / argon atmosphere. The temperature was raised to 1350 ° C within 270 min, and the temperature was kept at this temperature for 30 min. Then, the temperature was lowered to 150 ° C within 240 min, and the temperature was kept at this temperature for 300 min before sintering to obtain a solid electrolyte Li 6.5 LqCy 1.5 Ta 0.5 O 12 .
[0066] S2, grinding the sintered material into fine particles with a particle size of about 1000-1200 nm, and then ultrasonically dispersing them in a solvent with a solid-liquid mass ratio of 1:50, and stirring to obtain a suspension; the solvent is deionized water and anhydrous ethanol prepared in a volume ratio of 1:9; S3. Transferring the container containing the suspension to a mold filled with liquid nitrogen, wherein a copper heat conductive plate extending out of the liquid nitrogen surface is provided in the liquid nitrogen, and the container is placed on the copper heat conductive plate for freezing, so that ice crystals in the suspension grow vertically from bottom to top to obtain a single-oriented gel skeleton; freeze-drying the single-oriented gel skeleton to obtain an aerogel; sintering the aerogel in an inert atmosphere and / or a nitrogen atmosphere, heating the temperature to 400°C at a heating rate of 2°C / min and keeping the temperature for 4 hours to obtain a porous solid electrolyte, and grinding to obtain oxide particles with a particle size of 1000~1200nm.
[0067] S4, 0.1g oxide particles were mixed with 0.4g PEO and 6.4g acetonitrile for 12 hours, and a conventional coating method was used to prepare a thin film, and the film was dried to obtain a thin film. Specifically, a 200μm coater was used to coat on a smooth glass plate, 2g was coated each time, and the film was dried and then coated again for a total of three times. After drying, the film was dried in a vacuum oven at 60°C for 3 hours. The obtained film was cut into 19mm discs to obtain a porous composite solid electrolyte membrane.
[0068] S5. Add electrolyte (LB037: 1.0M LiPF6in EC:DEC:EMC=1:1:1 Vol%) dropwise into the porous composite solid electrolyte membrane to form a composite gel electrolyte membrane.
[0069] Example 6 A method for preparing a composite gel electrolyte membrane, comprising: S1. 2.64 g of lithium carbonate, 4.89 g of lanthanum oxide, 1.86 g of zirconium oxide, 1.1 g of tantalum oxide, and 30 g of isopropanol were ball-milled in a ball mill at a speed of 400 rpm for 1200 min. The ball-milled materials were placed in an oven and dried at 70 ° C. After drying, they were ground into fine particles and sintered in a muffle furnace in a nitrogen / argon atmosphere. The temperature was raised to 1350 ° C within 270 min, and the temperature was kept at this temperature for 30 min. Then, the temperature was lowered to 150 ° C within 240 min, and the temperature was kept at this temperature for 300 min before sintering to obtain a solid electrolyte Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 .
[0070] S2, grinding the sintered material into fine particles with a particle size of about 1000-1200 nm, and then ultrasonically dispersing them in a solvent with a solid-liquid mass ratio of 1:50, and stirring to obtain a suspension; the solvent is deionized water and anhydrous ethanol prepared in a volume ratio of 1:9; S3. Transferring the container containing the suspension to a mold filled with liquid nitrogen, wherein a copper heat conductive plate extending out of the liquid nitrogen surface is provided in the liquid nitrogen, and the container is placed on the copper heat conductive plate for freezing, so that ice crystals in the suspension grow vertically from bottom to top to obtain a single-oriented gel skeleton; freeze-drying the single-oriented gel skeleton to obtain an aerogel; sintering the aerogel in an inert atmosphere and / or a nitrogen atmosphere, heating the temperature to 400°C at a heating rate of 2°C / min and keeping the temperature for 4 hours to obtain a porous solid electrolyte, and grinding to obtain oxide particles with a particle size of 1000~1200nm.
[0071] S4, 0.3g oxide particles were mixed with 0.4g PEO and 6.4g acetonitrile for 12 hours, and a conventional coating method was used to prepare a thin film, and the film was dried to obtain a thin film. Specifically, a 200μm coater was used to coat on a smooth glass plate, 2g was coated each time, and the film was dried and then coated again for a total of three times. After drying, the film was placed in a vacuum oven at 60°C for 3 hours. The obtained film was cut into 19mm discs to obtain a porous composite solid electrolyte membrane.
[0072] S5. Add electrolyte (LB037: 1.0M LiPF6in EC:DEC:EMC=1:1:1 Vol%) dropwise into the porous composite solid electrolyte membrane to form a composite gel electrolyte membrane.
[0073] The composite gel electrolyte membranes prepared in Examples 2 to 6 were respectively assembled into semi-solid batteries according to the semi-solid battery assembly method of Example 1.
[0074] The semi-solid batteries assembled with the composite gel electrolyte membranes prepared in Examples 2 to 6 were subjected to charge and discharge cycles at 25°C, 2.7V to 4.3V, and 0.5C, and the cycle results are shown in Table 1. As can be seen from Table 1, the batteries assembled with the composite gel electrolyte membranes prepared in each example have good charge and discharge performance and cycle performance, and the amount of oxide solid electrolyte particles added has a more obvious effect on the battery.
[0075] Table 1 The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a composite gel electrolyte membrane, characterized in that: include: S1, dispersing oxide solid electrolyte particles in a solvent to obtain a suspension; The suspension is transferred to an environment containing liquid nitrogen for freezing, so that ice crystals grow vertically from bottom to top in the suspension to obtain a single-oriented gel skeleton; S2, freeze-drying the single-oriented gel skeleton to obtain an aerogel; sintering the obtained aerogel under a protective atmosphere to obtain a porous solid electrolyte, and grinding the porous solid electrolyte to obtain modified solid electrolyte particles; S3, mixing and stirring the modified solid electrolyte particles, PEO and solvent to obtain slurry, preparing the slurry into a film, and drying the film to obtain a porous composite solid electrolyte membrane; and dripping an electrolyte into the porous composite solid electrolyte membrane to obtain a composite gel electrolyte membrane.
2. The method for preparing a composite gel electrolyte membrane according to claim 1, characterized in that: In step S1, the particle size of the oxide solid electrolyte particles is 1-1.2 μm; In step S1, the dispersion is mechanical stirring dispersion or ultrasonic dispersion; In step S1, the solvent is a mixed solution prepared by mixing water and an organic solvent in a volume ratio of 1:8-9; the organic solvent is at least one of anhydrous ethanol and N-methylpyrrolidone; In step S1, the solid-liquid mass ratio of the suspension is 1:40-50.
3. The method for preparing a composite gel electrolyte membrane according to claim 1, characterized in that: In step S1, the suspension is transferred to an environment containing liquid nitrogen and frozen so that ice crystals grow vertically from bottom to top in the suspension to obtain a single-oriented gel skeleton, which includes: transferring a container containing the suspension to a mold filled with liquid nitrogen, wherein a heat conducting plate or a heat conducting platform extending out of the liquid nitrogen surface is provided in the liquid nitrogen, and the container is placed on the heat conducting plate or the heat conducting platform, and after freezing, a single-oriented gel skeleton is obtained.
4. The method for preparing a composite gel electrolyte membrane according to claim 1, wherein: In step S2, the sintering temperature is 200-500°C; In step S2, the sintering heat preservation time is 3 to 5 hours; In step S2, the sintering heating rate is 2-4°C / min; In step S2, the protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere.
5. The method for preparing a composite gel electrolyte membrane according to claim 1, characterized in that: In step S3, the mass ratio of the modified solid electrolyte particles to PEO is 1-3:4; In step S3, the particle size of the modified solid electrolyte particles is 1-1.2 μm; In step S3, in the slurry, the mass of the solvent is 12 to 20 times the mass of PEO; In step S3, the solvent is any one of acetonitrile, tetrahydrofuran, ethylene glycol and N-methylpyrrolidone.
6. The method for preparing a composite gel electrolyte membrane according to claim 1, characterized in that: In step S1, the oxide solid electrolyte is Li 7-z LqCy 2-z Ta z O 12 , where the value of z is 0≤z≤1.
7. The method for preparing a composite gel electrolyte membrane according to claim 6, characterized in that: In step S1, the method for preparing the oxide solid electrolyte particles comprises: mixing, ball-milling, sintering and grinding the metal sources corresponding to the metal elements contained in the oxide solid electrolyte.
8. The method for preparing a composite gel electrolyte membrane according to claim 1, characterized in that: Step S3 also includes the step of cutting the porous composite solid electrolyte membrane; In step S3, the film is prepared by any one of a casting method, a coating method, and a solution method.
9. A composite gel electrolyte membrane, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: The porous composite gel electrolyte membrane according to claim 9 is included.